2015
DOI: 10.1364/oe.23.006313
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of angle of arrival fluctuations for optical waves’ propagation through weak anisotropic non-Kolmogorov turbulence

Abstract: Analytical expressions for the variance of angle of arrival (AOA) fluctuations based on the Rytov approximation theory are derived for plane and spherical waves' propagation through weak anisotropic non-Kolmogorov turbulence atmosphere. The anisotropic spectrum model based on the assumption of circular symmetry in the orthogonal plane throughout the path is adopted and it includes the same degree of anisotropy along the direction of propagation for all the turbulence cells size in the inertial sub-range. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…(8), (21), and (26) leads to a closed-form expression for the near-field two-frequency MCF of Gaussian-beam pulses propagating along a horizontal line-ofsight path in anisotropic atmospheric turbulence, Similarly, its far-field counterpart is given by the combination of Eqs. (8), (22), and (26).…”
Section: Two-frequency Mcf For Gaussian-beam Pulsesmentioning
confidence: 99%
See 1 more Smart Citation
“…(8), (21), and (26) leads to a closed-form expression for the near-field two-frequency MCF of Gaussian-beam pulses propagating along a horizontal line-ofsight path in anisotropic atmospheric turbulence, Similarly, its far-field counterpart is given by the combination of Eqs. (8), (22), and (26).…”
Section: Two-frequency Mcf For Gaussian-beam Pulsesmentioning
confidence: 99%
“…As a result, numerous efforts have been made to understand the effects of anisotropy of turbulence on various aspects of optical-wave propagation including beam wander, beam broadening, angleof-arrival fluctuations, scintillations, log-amplitude correlation function, and so on [15][16][17][18][19][20][21]. Also, the impact of anisotropy on temporal broadening of narrowband optical pulses has recently been investigated in the strong-turbulence limit [10].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical expressions for the temporal power spectra of optical waves have been derived for weak and moderate to strong isotropic nonKolmogorov turbulence [7,8]. However, both experimental and theoretical results have shown that the atmospheric turbulence can also be anisotropic [3,[9][10][11][12][13][14][15][16][17][18][19][20][21]. Grechko et al [11] reported a strong anisotropy in the middle atmosphere from experimental observations of star scintillation.…”
Section: Introductionmentioning
confidence: 99%
“…For weak anisotropic non-Kolmogorov turbulence, the researchers have derived theoretically a series of turbulence effects models, including the long-term beam spread, variance of irradiance fluctuations, log-amplitude correlation function (it equals one fourth of the spatial covariance function of irradiance fluctuations), variance of AOA fluctuations, and modulation transfer function [18][19][20][21][22]. When turbulence strength increases beyond the weak turbulence regime, Andrews et al [23] developed several mathematical turbulence effect models (longterm spot size, spatial coherence radius, and variance of irradiance fluctuations) for Gaussian beam propagating through moderate to strong anisotropic non-Kolmogorov turbulence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation